(untitled) (University of Warwick Press, 2022)
Dialogical-participatory mapping is based on the participatory co-production of geographic data by citizens, researchers, public authorities and other interested parties. In this manual, through provoking a critical reflection on the practices this methodology involves, we attempt to introduce a holistic critical and interactive pedagogical approach. Methodologically, we apply several collaborative activities and tools based on local narratives and knowledge and spearheaded by spatial mapping related methods. Dialogical-participatory mapping, is a mapping methodology designed by researchers from the Waterproofing Data and further explored and consolidated through the ESRC IAA-funded project ‘Accelerating the impact of citizen-generated data for improving the monitoring and management of catastrophic flooding’. The project was led by the University of Warwick (United Kingdom) in partnership with the School of Business Administration of Fundação Getulio Vargas (FGV EAESP), the National Centre for Monitoring and Alerting for Natural Disasters (Cemaden) and the NGO TETO Brazil. As an idealised and systematised method, its main objective is to strengthen situational awareness of the reality within the community, with geographic data consolidating as a significant component, with truly social and transformative value. This mapping process consists of several steps, which in many cases may vary according to the needs of the different communities. In other words, there is a dialogic interaction between researchers and the citizens participating in the mapping process, in the pursuit of practices that can be significant for the accurately representing their existent and emerging themes of interest. These so-called ‘generative themes’ are the starting point of the dialogical-participatory mapping process, emerging from popular knowledge, extracted from the everyday life of local citizens, which means that such themes are distinguished and defined by the community members themselves. Between April and June 2022, researchers and research assistants from the international project consortium carried out a dialogical-participatory mapping exercise in three Brazilian states: Acre (AC), Minas Gerais (MG) and São Paulo (SP). The communities investigated were: 06 de Agosto neighbourhood in Rio Branco (AC), Guarani Kaiowá Occupation in Contagem (MG) and Cai Cai community in São Paulo (SP). This manual is intended for the academic community, for social innovation institutions and self-managed bodies focused on direct social action through collective production of data with the community members. The approaches, methodologies and tools that were part of the mapping process in the different urban contexts are briefly presented, so as to enable the replication of this method at various instances not only within the Brazilian context but across other communities in Latin America and beyond. Uma versão em português está disponível.